2015
DOI: 10.1128/jb.02263-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome Instability Mediates the Loss of Key Traits by Acinetobacter baylyi ADP1 during Laboratory Evolution

Abstract: Acinetobacter baylyi ADP1 has the potential to be a versatile bacterial host for synthetic biology because it is naturally transformable. To examine the genetic reliability of this desirable trait and to understand the potential stability of other engineered capabilities, we propagated ADP1 for 1,000 generations of growth in rich nutrient broth and analyzed the genetic changes that evolved by whole-genome sequencing. Substantially reduced transformability and increased cellular aggregation evolved during the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 51 publications
1
50
1
Order By: Relevance
“…We and others have found that mutants with reduced transformability arise and take over populations of ADP1 during long-term evolution experiments (14,15). This result was thought to occur due to a strong selective pressure to lose competence, either a direct cost for producing the DNA uptake apparatus or a deleterious effect from active DNA uptake.…”
Section: Importancementioning
confidence: 99%
See 4 more Smart Citations
“…We and others have found that mutants with reduced transformability arise and take over populations of ADP1 during long-term evolution experiments (14,15). This result was thought to occur due to a strong selective pressure to lose competence, either a direct cost for producing the DNA uptake apparatus or a deleterious effect from active DNA uptake.…”
Section: Importancementioning
confidence: 99%
“…Strains in this study were derived from an A. baylyi ADP1 evolution experiment (15). Growth conditions were incubation at 30°C with orbital shaking at 140 rpm over a 1-inch diameter in LB (10 g/liter tryptone, 5 g/liter yeast extract, and 10 g/liter NaCl).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations